2005
DOI: 10.1111/j.1742-4658.2005.04553.x
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations as a cause of metachromatic leukodystrophy

Abstract: Metachromatic leukodystrophy is a lysosomal storage disorder caused by a deficiency of arylsulfatase A (ASA). Biosynthesis studies of ASA with various structure‐sensitive monoclonal antibodies reveal that some epitopes of the enzyme form within the first minutes of biosynthesis whereas other epitopes form later, between 10 and 25 min. When we investigated 12 various ASAs, with amino acid substitutions according to the missense mutations found in metachromatic leukodystrophy patients, immunoprecipitation with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Since sphingolipids play a key role in myelin synthesis, the disease affects both branches of the nervous systems: the peripheral and the central. MLD is caused by a deficiency in the enzyme, arylsulfatase A (ARSA) (Poeppel et al, 2005). It has been demonstrated that the enzyme activity in the majority of cases declines to the level of 10% or lower compared to that of unaffected controls.…”
Section: Cns Clinical Trials Utilizing Retroviral Vectorsmentioning
confidence: 99%
“…Since sphingolipids play a key role in myelin synthesis, the disease affects both branches of the nervous systems: the peripheral and the central. MLD is caused by a deficiency in the enzyme, arylsulfatase A (ARSA) (Poeppel et al, 2005). It has been demonstrated that the enzyme activity in the majority of cases declines to the level of 10% or lower compared to that of unaffected controls.…”
Section: Cns Clinical Trials Utilizing Retroviral Vectorsmentioning
confidence: 99%
“…Though several missense mutations have been identified, few of them have been biochemically characterized 10,43. Most missense mutations result in misfolded mutant ASA that is early selected for the ER-associated degradation (ERAD) pathway and targeted to the ubiquitin-proteasome system 44. Therefore, small amounts of partially folded and/or misfolded mutant ASA pass the ER post-translational quality control and ultimately reach the lysosomal compartment, resulting in the residual ASA enzymatic activity 45.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by several missense mutations on Chromosome 22, causing defects of the enzyme arylsulfatase A ( ARSA ) [29]. One of the SNPs with dbSNP ID that is the supposedly responsible mutation for MLD, is a C → G substitution, leading to an amino acid change of T h r e o n i n e → S e r i n e in the corresponding protein ARSA .…”
Section: Resultsmentioning
confidence: 99%